1986
DOI: 10.1159/000132298
|View full text |Cite
|
Sign up to set email alerts
|

Owl monkey gene mapping: the assignment of gene loci for catalase, β-globin gene cluster, HRAS1, insulin, and parathyroid hormone

Abstract: Using somatic cell genetics and Southern blot hybridization, we have mapped five structural genes in the owl monkey, coding for catalase (CAT), the β-globin gene cluster (HBBC), c-Ha-ras 1 (HRAS1), insulin (INS), and parathyroid hormone (PTH). All five loci are mapped to chromosome 19 of karyotype VI (2n = 49,50) of the owl monkey; CAT, HBBC, INS, and PTH can be assigned to chromosome 4 of karyotype V (2n = 46), while CAT and HBBC can be assigned to chromosome 2 of karyotype III (2n = 53). Using in situ hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In a recent study of primate genomic evolution, it was shown that CAT, HBBC, HRAS, INS, and PTH are all located on the same chromosome in the owl monkey (27). A similar conservation has been noted in the rat, where HRAS, INS, HBBC, LDHA, CALC, and PTH all have been assigned to chromosome 1 (35).…”
Section: Discussionmentioning
confidence: 66%
“…In a recent study of primate genomic evolution, it was shown that CAT, HBBC, HRAS, INS, and PTH are all located on the same chromosome in the owl monkey (27). A similar conservation has been noted in the rat, where HRAS, INS, HBBC, LDHA, CALC, and PTH all have been assigned to chromosome 1 (35).…”
Section: Discussionmentioning
confidence: 66%
“…The same hybrid cell lines had been used for other owl mon key gene mapping studies reported previously (Ma, 1983;Ma et al. 1986).…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme-digested DNA was blotted on nitrocellulose or Nylon membranes and hybridized with a hexamcr-labeled or nick-translated probe. Hybridization was performed at 45-65 C in 5 x NaCl sodium citrate, and the filters were washed under stringent conditions as described previously (Ma et al, 1986).…”
Section: Methodsmentioning
confidence: 99%